First-/last-mile experience matters: The influence of the built environment on satisfaction and loyalty among public transit riders - Park, Keunhyun; Farb, Anna; Chen, Shuolei (Transport policy, 2021)
Public transit authorities have enhanced the travel experience to promote ridership and customer loyalty. Previous studies about satisfaction and loyalty of transit riders, however, give less attention to out-of-vehicle environments such as walking/biking routes, transfer comfort, and traffic and crime safety conditions. The first-mile and last-mile problem—distance traveled before and after using transit—is a well-known barrier of transit use, but an empirical study about how people experience it is lacking. Thus, this study aims to explore how transit riders experience out-of-vehicle environments—access, transfer, and egress—and how their experience is related to overall satisfaction and loyalty to transit service. We conducted a questionnaire survey of people (n = 445) living in areas served by the Utah Transit Authority and analyzed the responses through an Importance-Satisfaction analysis and a path analysis, a type of structural equation modeling. A descriptive analysis demonstrates complex first-mile travel patterns: driving is the most common mode to start a transit-involved trip (68.5%), and one-third of transit riders transfer more than once before riding on a transit (e.g., driving → walking → transit). Results from the Importance-Satisfaction analysis highlight both traffic and crime safety concerns at transit stops and walking routes as a critical out-of-vehicle element most in need of improvement. A path analysis result confirms that out-of-vehicle environments—in particular, safety and transfer experience—influence customer satisfaction and loyalty more than in-vehicle and system-related factors do. This paper concludes with practical suggestions for multiple agencies (e.g., public transit, transportation, and urban planning), including urban design strategies, land use-transit integration, and multi-modal integration. •We find complex first-mile travel patterns with multiple transfers.•Driving is the most common mode to start a transit-involved trip.•Traffic and crime safety issues are most in need of improvement.•Out-of-vehicle environments influence customer satisfaction and loyalty.